Metadata of Patent Information in the Value Assessment of New Technology Solutions - Monika Bolińska; Paweł Dykas; Rafał Wisła (Journal for Perspectives of Economic Political and Social Integration)
This study aims to discuss the possibility of an aggregated value assessment of a new technology solution on various levels: an entity (organization), specific technology field, regional economy, national economy, the economy of an integration group, and to test that assessment method using a transnational approach. In addition to testing the possibility and purposefulness of an aggregated assessment of new technology solutions in a group of countries, the study is aimed to test the hypothesis on a large technology quality gap between the German economy and those of other member states of the European Union.